DIAGNOSTIC PERFORMANCE OF ENDOSCOPIC ULTRASOUND FINE NEEDLE BIOPSY IN DIAGNOSTIC VATER CANCER IN K HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Background: This study aimed to describe the clinical features, endoscopic ultrasound imaging features, and outcomes of endoscopic ultrasound-guided fine-needle biopsy in the diagnosis of ampullary cancer at K Hospital. Population and methods: A retrospective cross-sectional descriptive study on 46 patients with suspected ampullary carcinoma detected by abdominal ultrasound or computed tomography, who underwent endoscopic ultrasound guided fine-needle biopsy at K Hospital. Histopathological results obtained from biopsy were compared with postoperative pathological findings from January 2021 to June 2025. Results: Among 46 patients who underwent diagnostic biopsy, the result confirmed ampullary carcinoma in 43 patients, accounting for 93,5%. The mean age was 62.91 ± 9.33 years. The most common clinical symptom was jaundice, present in 90,7% of cases. An average of puncture was 1.32 procedures per patient and the mean number of needle passes per lesion was 6.72. Macroscopic on-site evaluation (positive MOSE) was achieved in 76.1% of cases. After the procedure, one patient experienced localized bleeding at the biopsy site, and no major complications were detected. The sensitivity, specificity, PPV, NPV, and diagnostic accuracy of EUS-guided biopsy for diagnosing ampullary carcinoma were 93%; 66,7%; 40% and 91,3%, respectively. Conclusion: Endoscopic ultrasound-guided fine needle biopsy is a safe technique with high sensitivity and positive predictive value in patient suspected ampullary carcinoma. However, in cases of negative biopsy or paucicellular results still require correlation with clinical and paraclinical findings, or repeat biopsy to confirm the diagnosis.
Keywords: Ampullary carcinoma, endoscopic ultrasound, Endoscopic ultrasound with fine-needle biopsy.